Micro-Pillar Integrated Dissolving Microneedles for Enhanced Transdermal Drug Delivery - Lee, Seunghee (Pharmaceutics, 2019)
The dissolving microneedle (DMN) patch is a transdermal delivery system, containing arrays of micro-sized polymeric needles capable of encapsulating therapeutic drugs within their matrix and releasing them into the skin. However, the elastic properties of the skin prevent DMNs from complete insertion and accurate delivery of encapsulated compounds into the skin. Moreover, the adhesive materials used in patches may cause skin irritation, inflammation, and redness. Therefore, we developed a patchless, micro-pillar integrated DMN (P-DMN) that is simple to fabricate and enhances transdermal drug delivery compared with traditional DMN patches. The micro-pillars were made of polymethyl methacrylate at a height of 300 μm and a base diameter of 500 μm. To fabricate P-DMNs, we employed hyaluronic acid, which is a widely used derma filler and plays a role in tissue re-epithelialization. We demonstrate that utilizing P-DMNs significantly improves the delivery efficiency of an encapsulated drug surrogate (91.83% ± 7.75%) compared with traditional DMNs (64.86% ± 8.17%). Interestingly, P-DMNs remarkably increase the skin penetration accuracy rate of encapsulated drugs, up to 97.78% ± 2.22%, compared with 44.44% ± 7.85% in traditional DMNs. Our findings suggest that P-DMNs could serve as a highly accurate and efficient platform for transdermal delivery of various types of micro- and macro-biomolecules.